Development of Physics Learning Assessment Instrument in Project-Based Learning Model to Improve 4C Skills - Nurul Azmi; Festiyed Festiyed (Postgraduate, University of Mataram, 2023)
The objectives of this study were 1) to produce a physics learning assessment instrument in the PjBL model to improve students' 4C skills with valid criteria, 2) to test the practicality of the physics learning assessment instrument in the PjBL model to improve students' 4C skills. This type of research is research and development using the ADDIE model which consists of the analyze stage, design stage, and is limited to the develop stage. The object of research is the physics learning assessment instrument in the PjBL model to improve 4C skills. The data collection instruments used are validation sheets, practicality test sheets for educators and students. The data analysis technique used is validity analysis and practicality analysis of the use of assessment instruments. Based on the data analysis that has been done, two research results can be stated. First, the average value of the validity of the PjBL model assessment instrument is 0.85 valid criteria. Second, the average value of the practicality test of the PjBL model assessment instrument for educators and students is 90.00% and 86.15%, respectively, very practical criteria.